Klucz ze Śladkowa Górnego, gm. Zgierz - Jadczykowa, Irena (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
The excavations at Śladków Górny, Zgierz commune, conducted by the writer in 1981-1984 on behalf of the Archaeological and Ethnographical Museum in Łódź revealed remains of settlements from the beginnings of the Przeworsk culture and from the Early Middle Ages. The site lies on a sandy and gravelly eminence situated just off the village and devasted by a pre-war gravel-pit. An area of 1175 m2 was explored yielding remains of houses and economic features of both periods. Among the Late La Téne features of particular interest is house I containing a dog’s skeleton as a foundation sacrifice and a hearth. 1.8 m in diameter and over 1 m deep, comprising trough-shaped layers of burnt matter and a very big stone. It is possible that the hearth had another than a purely domestic function. Apart from pottery, early medieval finds comprised a spearhead, an awl, a „strike-a-light”, knives, temple rings and a key shaped as the letter T. The key comes from the cultural layer in section 35 where materials from both settlements were found. Keys of that type range in date from La Téne III (e.g. ancient Bibracte) to the Late Middle Ages and therefore the date of the find in question has been established by the results of a spectographical analysis. The composition of the metal used in the production of the key and the finish of its surface are near-identical with those of the key found at the early medieval earthwork at Czerchów, only 10 km away.